PEMBERITAAN MENGENAI POLIGAMI DI SURAT KABAR NASIONAL (ANALISIS FRAMING TERHADAP PEMBERITAAN POLIGAMI DI SURAT KABAR HARIAN NASIONAL SEPUTAR INDONESIA EDISI DESEMBER 2006 - JANUARI 2007) - Zia El Muttaqin; Susilastuti DN; Christina Rochayanti (Jurnal Ilmu Komunikasi, 2008)
Polygamy matter has been some hot issue which is deliberated by many people, espe- cially after the confession of ustadz Abdullah Gymnastiar, the leader of Daarut Tauhid Geger, Kalung Girang, Jawa Barat, school of Koranic studies; who is married to a widow named Alfarini Eridani to be his second wife. The marriage of Aa Gym divided people into two sides, one side supported, and the other refused, while the government was also involved in. By means of mass media, then it would be seen how the attitude tendency of a media in viewing polygamy issue would be exacerbate, neutralize, or supportive through framing analyzes. There is three topics used in this research, they are: the first topic: The Cause of Polygamy Press Spread on Seputar Indonesia Media, the second topic: Reaction by People Due to Polygamy on Mass Media, the third topic: The Government’s Role in Encountering the Polygamy Issue on Mass Media. The research methods used are framing analysis Pan Model and Kosicki, which is by syntax analyzing (headline, lead, background, source quotation, closing), script (5W+1H), thematic (detail, co- herence, sentence form, pronoun), rhetoric, (lexicon, metaphor, photograph, graphic, words). The news researched is six news, which is each 2 news based on those three topics. The research result showed that initially the newspaper Seputar Indonesia endeavored to show neutral frame which was indifferent, by consideration that polygamy is some right for everyman who is desire and able to polygamy, while those who refuse is some part of democratic life. However, the frame of Seputar Indonesia has begun to shift to exacerbate the conflict in society. Seputar Indo- nesia showed the frame manner to legalize of polygamy, through news selection and press pat- tern one news one side, which is contained smoothly and obscurely, by indirectly state its support through press on Seputar Indonesia newspaper.